Dorsal striatal hypoconnectivity predicts antipsychotic medication treatment response in first‐episode psychosis and unmedicated patients with schizophrenia - Eric A. Nelson; Nina V. Kraguljac; Jose O. Maximo; William Armstrong; Adrienne C. Lahti (Brain and Behavior, 2022)
Abstract Introduction The dorsal striatum, comprised of the caudate and putamen, is implicated in the pathophysiology of psychosis spectrum disorders. Given the high concentration of dopamine receptors in the striatum, striatal dopamine imbalance is a likely cause in cortico‐striatal dysconnectivity. There is great interest in understanding the relationship between striatal abnormalities in psychosis and antipsychotic treatment response, but few studies have considered differential involvement of the caudate and putamen. This study's goals were twofold. First, identify patterns of dorsal striatal dysconnectivity for the caudate and putamen separately in patients with a psychosis spectrum disorder; second, determine if these dysconnectivity patterns were predictive of treatment response. Methods Using resting state functional connectivity, we evaluated dorsal striatal connectivity using separate bilateral caudate and putamen seed regions in two cohorts of subjects: a cohort of 71 medication‐naïve first episode psychosis patients and a cohort of 42 unmedicated patients with schizophrenia (along with matched controls). Patient and control connectivity maps were contrasted for each cohort. After receiving 6 weeks of risperidone treatment, patients’ clinical response was calculated. We used regression analyses to determine the relationship between baseline dysconnectivity and treatment response. Results This dysconnectivity was also predictive of treatment response in both cohorts. Discussion These findings suggest that the caudate may be more of a driving factor than the putamen in early cortico‐striatal dysconnectivity.